Longitudinal associations between temperament and socioemotional outcomes in young children: The moderating role of RSA and gender. Issue 1 (16th November 2014) - Morales, Santiago; Beekman, Charles; Blandon, Alysia Y.; Stifter, Cynthia A.; Buss, Kristin A.
ABSTRACT Temperament is an important predictor of socioemotional adjustment, such as externalizing and internalizing symptoms. However, there is not a one‐to‐one correspondence between temperamental predispositions and these outcomes, implying that other factors also contribute to the development of internalizing and externalizing problems. Self‐regulation is believed to interact with temperament, and has been studied as a predictor for later socioemotional outcomes. Respiratory sinus arrhythmia (RSA) is a psychophysiological measure of self‐regulation that has been studied as a moderator of risk. The primary aim of the present study was to test if RSA baseline and RSA reactivity would moderate the link between temperament and socioemotional outcomes. Mothers reported the temperament of their infants (20 months; N = 154), RSA was collected at 24‐ and 42‐months, and mothers reported externalizing and internalizing behaviors at kindergarten entry. RSA baseline and RSA reactivity moderated the relation between exuberant temperament and externalizing behaviors. However, these results were only significant for girls, such that high RSA baseline and greater RSA suppression predicted more externalizing behaviors when exuberance was high. Fearful temperament predicted later internalizing behaviors, but no moderation was present. These results are discussed in light of recent evidence regarding gender differences in the role of RSA as a protective factor for risk. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 57: 105–119, 2015.